THE MEDIATING ROLE OF CHATBOT INITIAL TRUST IN ENHANCING CUSTOMER LOYALTY, ENGAGEMENT, AND USAGE INTENTION - Luthfi Fakhri Ramadhan; Rifelly Dewi Astuti (Jurnal Apresiasi Ekonomi, 2025)
In the digital era, chatbots have become essential tools for companies to enhance communication efficiency with customers, particularly through popular platforms such as WhatsApp. As the adoption of this technology increases, understanding the factors that shape users initial trust becomes crucial. This study aims to analyze the influence of perceived ease of use, compatibility, performance expectancy, social influence, and perceived risk on initial trust, as well as its impact on chatbot usage intention, customer engagement, customer satisfaction, and customer loyalty. The research model was developed based on an integration of the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Diffusion of Innovation (DOI), using a quantitative approach. A total of 223 respondents participated in a survey distributed to users of banking chatbots via WhatsApp in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived ease of use and social influence have a significant positive effect on initial trust, while compatibility, performance expectancy, and perceived risk do not have a significant effect. However, performance expectancy was found to have a direct and significant influence on chatbot usage intention. Initial trust significantly influences usage intention, customer engagement, customer satisfaction, and customer loyalty. Furthermore, customer satisfaction also has a significant effect on customer loyalty.